The Influence of Company Quality in Product Development - Junnior Sohilait; Joachim Siahaya; Gideon Penggu; Injilia Titjo; Mutiara Mamonto; Jonathan Langoi (Syntax Corporation Indonesia, 2025)
This abstract discusses the impact of a company's management quality on product development, which is a key factor in business success in today's competitive era. This study analyzes the relationship between management quality and the effectiveness of new product development, as well as how it affects the overall performance of the company. High management qualities, which include visionary leadership, good strategic planning, and effective resource management, are proven to accelerate the innovation process and improve product quality. In addition, good management also plays a role in overcoming obstacles that arise during product development, such as technical constraints and dynamic market changes. This study uses a case study method on several companies that have successfully developed innovative products, and finds that companies with quality management tend to have more efficient, more adaptive product development cycles to market changes, and able to produce products that are more in line with consumer needs. The results of this study emphasize the importance of the role of quality management in supporting the success of product development, which in turn increases the company's competitiveness and profitability. These findings can be a reference for companies in strengthening their management to drive product innovation and business growth.